A study on motivation factors that influence job satisfaction among workers at Molex (M) Sdn. Bhd. / Nurshafaradila Mohammed Daud and Farah Nadiah Mohamed Affandi - Mohammed Daud, Nurshafaradila; Mohamed Affandi, Farah Nadiah (Faculty of Business and Management, 2013)
Employee’s satisfaction is vital in an organization. Human Capital is one of the important assets to the organization. It is very important for organizations to retain their employee’s satisfaction to make their company competitive advantage than others. It is important for the organizations to design the good motivation system to encourage employees to perform in the better condition as well as to help the company growth. The employees in the company come from ages range 18 to 60 years and above and from different races which consists of Malay, Chinese, Indian, and other races. Data is collected through questionnaires distributed to 70 employees in Molex (M) Sdn. Bhd. using simple random sampling. This research study will be used multiple regression analysis, Pearson correlation analysis, reliability analysis and frequency distribution in order to identify and support the relationships between dependent and independent variables. This research studies on four motivation factors affecting job satisfaction which are recognition, achievement, salary or reward and supervision at Molex (M) Sdn. Bhd. Overall of this study will indicate the most influential independent variables or factors to give an effect to the job satisfaction at Molex (M) Sdn. Bhd. This study indicates to be beneficial to the company. This will help them gained awareness on employee’s motivation at Molex (M) Sdn. Bhd.